2010
DOI: 10.1002/jcu.20781
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between brachial artery flow‐mediated dilatation, high sensitivity C‐reactive protein, and uterine artery doppler velocimetry in women with pre‐eclampsia

Abstract: These findings suggest that maternal serum hs-CRP levels increase with the severity of pre-eclampsia, reflecting endothelial dysfunction and constituting a potential marker of pathological utero-placental perfusion, with a high risk for fetal growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…The 14 cross-sectional studies that were eligible for the meta-analysis 23, 3041 included 333 preeclamptic women and 467 non-preeclamptic pregnant women (Tables S2, S6). Five additional studies were included in the qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The 14 cross-sectional studies that were eligible for the meta-analysis 23, 3041 included 333 preeclamptic women and 467 non-preeclamptic pregnant women (Tables S2, S6). Five additional studies were included in the qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In pre-eclamptic pregnancies complicated by IUGR, FMD is further reduced [44, 48]. FMD is a non-invasive marker of endothelial function and, as such, NO bioavailability.…”
Section: Effect Of Gsnor Inhibitors On Endothelial Functionmentioning
confidence: 99%
“…Most studies report lower FMD in women with preeclampsia, compared to normotensive pregnant women [70, 66, 71, 72, 65, 52, 76, 77]. However, a few studies found no differences [67, 61, 68].…”
Section: Fmd and Preeclampsiamentioning
confidence: 99%
“…FMD was lower in women with preeclampsia complicated by HELLP (hemolysis, elevated liver enzymes, low platelets) syndrome, eclampsia or stillbirth, compared to women who had preeclampsia without these complications [78]. FMD was also lower in preeclamptic women with an abnormal uterine artery Doppler at diagnosis, compared to preeclamptic women with a normal uterine artery Doppler [66]. However, FMD did not differ among women with normotensive pregnancies, mild preeclampsia and severe preeclampsia [67], or between women with preeclampsia and women with preeclampsia superimposed on chronic hypertension [79].…”
Section: Fmd and Preeclampsiamentioning
confidence: 99%